Coming to Terms with the Humanitarian Imperative in Iraq; Arabic translation of recommendationss - Hansen, Greg (Tufts Archival Research Center, 2008)
Unnamed translator. An Arabic translation of the Recommendations section of the report "Coming to Terms with the Humanitarian Imperative in Iraq".